Critical stress of high‐density polyethylene during stress and photo‐oxidative aging. Issue 10 (3rd July 2015) - Li, Yongliang; Liu, Wenliang; Ren, Xiancheng
<x xml:space="preserve">Abstract</x> The long‐term photo‐oxidative aging behavior of high‐density polyethylene (HDPE) under different tensile stress was studied using a stress‐aging apparatus. The aging behavior was investigated through the methods of the surface morphology observation, gel content measurement, Fourier transform infrared spectroscopy, and creep behavior. It was found that stress has influence on the development of cracks and stress induces cracking through creep deformation. With increasing stress, the cracking time decreases in a reversed S‐shape curve way, and there is a critical stress near 7 MPa where the cracking time has a maximum decreasing rate. Meanwhile, the creep deformation increases rapidly when the stress exceeds the critical stress. The critical stress of HDPE is about 20–25% of breaking strength, and HDPE with low comonomer content has good dimensional stability when the stress is less than the critical stress, while HDPE with high comonomer content has a good performance when the stress exceeds the critical stress. This study may be useful for the rational selection of HDPE for the sheath material of bridge cable. POLYM. ENG. SCI., 55:2277–2284, 2015. © 2015 Society of Plastics Engineers